Superior strength-ductility synergy in ultrafine-grained Al–5Mg alloy - Aydar M. Mavlyutov; Demid A. Kirilenko; Aleksandr A. Levin; Maxim Yu. Murashkin; Dinislam I. Sadykov; Tatiana S. Orlova (Journal of Materials Research and Technology)
In this study, a comprehensive investigation was conducted for the first time to systematically explore the impact of deformation-heat treatment (DHT) on the microstructure and mechanical properties of ultrafine-grained (UFG) Al–5Mg (wt.%) alloy. The UFG structure was formed by high pressure torsion (HPT) at room temperature (RT). The proposed DHT of the UFG alloy includes annealing at 150–230 °C and additional deformation by HPT at RT to 0.25–0.75 turns. As was demonstrated, annealing does not lead to an increase in the ductility of the UFG alloy, and subsequent additional deformation leads to the manifestation of the effect of deformation-induced softening: ductility increases from <1% to ∼5.5% while maintaining high strength (∼725 MPa). The resulting combination of strength and ductility significantly exceeds those reported for the other UFG Al–Mg alloy with comparable Mg concentrations, which were structured and treated by different methods. It was shown for the first time that annealing at 230 °C increases the degree of Mg segregation at grain boundaries and forms Mg-rich zones in triple junctions, and the subsequent small additional deformation does not significantly affect these parameters. Based on the microstructural changes during the DHT process, the physical reasons for the outstanding combination of strength and ductility are analyzed.